Pengaruh Susu Kedelai dan Bubur Kacang Hijau terhadap Lingkar Pinggang Wanita Pascamenopause - Syailawan, Fendie K.; Wiboworini, Budiyanti; Kartikasari, Lilik Retna (Media Kesehatan Masyarakat Indonesia, 2019)
Postmenopausal women are prone to obesity. Soy milk and mung bean porridge contain fiber and flavonoids which are beneficial as anti-obesity. This study aimed to analyze the effect of soy milk and mung bean porridge on waist circumference among postmenopausal women. This was an experimental study using pre-posttest with the control group. The study was conducted for 4 weeks from December 2018 to January 2019 in Serengan, Surakarta. Subjects were randomly divided into control group (n=10), soy milk (n=10) and combination of soy milk and mung bean porridge (n=10). Soy milk and mung bean porridge provided were 240 ml and 180 ml/day/person and given for 4 weeks, respectively. Data were then analyzed with paired t-test, one way ANOVA and Bonferroni test. There were no significant differences in the nutritional status, occupation and education level of the three groups. There was a significant reduction in waist circumference in both the soy milk and combination group compared to the control group (p<0.05). The mean decrease in waist cirumference was -2.40±2.23 cm in the soy milk group and -5.30±3.20 cm in the combination group. Soy milk and mung bean porridge can be alternative therapies to reduce waist circumference among postmenopausal women.